2019
DOI: 10.1002/jcsm.12424
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐driven changes link T cell frequency to muscle strength in people with cancer: a pilot study

Abstract: Background Tumour growth can promote the loss of muscle mass and function. This is particularly disturbing because overall survival is significantly reduced in people with weaker and smaller skeletal muscle. The risk of cancer is also greater in people who are immune deficient. Muscle wasting in mice with cancer can be inhibited by infusion of CD4 + precursor T cells that restore balanced ratios of naïve, memory, and regulatory T cells. These data are consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Of note, we found correlations between changes in lower limb muscle and handgrip strength and immunogenic markers, including CD8a. These results are confirmed by a recent pilot study from Narsale et al ( 36 ), who showed that naïve, memory, and regulatory T-cells correlate with muscle strength and performance, suggesting that engagement in muscular strengthening activities might have beneficial effects on inflammatory markers. We did not find a correlation between changes in BMI and inflammatory markers, as suggested by earlier research ( 37 ).…”
Section: Discussionsupporting
confidence: 74%
“…Of note, we found correlations between changes in lower limb muscle and handgrip strength and immunogenic markers, including CD8a. These results are confirmed by a recent pilot study from Narsale et al ( 36 ), who showed that naïve, memory, and regulatory T-cells correlate with muscle strength and performance, suggesting that engagement in muscular strengthening activities might have beneficial effects on inflammatory markers. We did not find a correlation between changes in BMI and inflammatory markers, as suggested by earlier research ( 37 ).…”
Section: Discussionsupporting
confidence: 74%
“…PNI is a reflect factor for nutritional and immune status of cancer patients, which is a meaningful prognostic factor in NPC patients (20,33). A possible reason for the above finding may be that stronger anticancer Tcell immunity may improve muscle quality and function through interaction with immune cells (34), it is more likely that a good muscle mass allows a better immune response, being a reserve for the production of acute-phase proteins. These results indicate that oncologists should screen and assess older cancer patients for sarcopenia and nutritional and functional status early in the course of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Muscle biopsies of patients with different cancers, most of whom had gastrointestinal cancers, showed a positive correlation between the abundance of CD3 + CD4 − cells (presumably CD8 + T cells) and muscle fibre cross-sectional area 81 . In a separate cohort of patients with cancer who showed early signs of muscle impairment, circulating levels of recent thymic migrant and effector memory CD8 + T cells were associated with increased muscle mass 82 . Meanwhile, the abundance of regulatory T (T reg ) cells and central memory T cells showed a negative correlation with muscle mass.…”
Section: Immune Cells In Cachexiamentioning
confidence: 92%